An Overview of 3D Printing In Construction (International Journal of Innovative Research in Engineering & Management, 2021)
Building is generally of the largest employment businesses in  the globe, as well as one of most significant providers of jobs.  For years, the industry has been plagued by low production  and limited technological advancements. The building sector  has lately been more interested in different automation, like  3D printing. printing in architecture has demonstrated to be  incredibly promise in regards of automation construction  procedures, and it has the capacity to save time, money, and  potentially risky people activities, among other things. A lot  of research has gone into better understanding present  advances, future prospects, and challenges related with large scale usage of 3D printing in construction projects. Since  building is an employment business, this study examines the  impact of increased 3D printing adoption on the labor market.  It has been revealed that 3D printers may reduce the quantity  of labor necessary, which might assist to alleviate the labor  shortages problem, especially in countries where building is  heavily dependent on immigrants. In countries where  construction is a big employment and labour is lower  expensive, however, 3D printing may not be beneficial.  Furthermore, professionals with specific understanding of this  novel technique will be required to employ 3D structure  manufacturing.
Keywords: 3D Printing; Additive Manufacturing; Construction; Workforce; Construction Labor